Guidelines of the International Headache Society for controlled trials of preventive treatment of chronic migraine in adults. (April 2018) - Tassorelli, Cristina; Diener, Hans-Christoph; Dodick, David W; Silberstein, Stephen D; Lipton, Richard B; Ashina, Messoud; Becker, Werner J; Ferrari, Michel D; Goadsby, Peter J; Pozo-Rosich, Patricia; Wang, Shuu-Jiun; ,
Background: Quality clinical trials form an essential part of the evidence base for the treatment of headache disorders. In 1991, the International Headache Society Clinical Trials Standing Committee developed and published the first edition of the Guidelines for Controlled Trials of Drugs in Migraine . In 2008, the Committee published the first specific guidelines on chronic migraine. Subsequent advances in drug, device, and biologicals development, as well as novel trial designs, have created a need for a revision of the chronic migraine guidelines. Objective: The present update is intended to optimize the design of controlled trials of preventive treatment of chronic migraine in adults, and its recommendations do not apply to trials in children or adolescents.